Human Development Report 2005 - United Nations Development Programme (United Nations, 2005)
The Human Development Report 2005 examines the scale of the challenge facing the world at the start of the ten year countdown to the 2015 Millennium Development Goals mark. The Report focuses on three pillars of cooperation, each of which is in urgent need of renovation. The first pillar is international aid; the MDG project has been compromised by chronic and sustained under-financing, allied to problems in aid quality. The second pillar is international trade; under the right conditions, trade can act as a powerful catalyst for human development. The ‘development round’ of World Trade Organization talks, launched in 2001, provided northern governments with an opportunity to create those conditions. The third pillar is that of security; violent conflict is a source of systematic human rights violation and a barrier to progress towards the MDGs that must be overcome.